2006
DOI: 10.1088/0268-1242/21/8/012
|View full text |Cite
|
Sign up to set email alerts
|

On the intersecting behaviour of experimental forward bias current–voltage (IV) characteristics of Al/SiO2/p-Si (MIS) Schottky diodes at low temperatures

Abstract: In this study, we have investigated the intersection behaviour of forward and reverse bias current-voltage (I-V ) characteristics of Al/SiO 2 /p-Si Schottky diodes in the temperature range of 79-325 K. The crossing of the experimental semi-logarithmic ln(I )-V curves appears as an abnormality when seen with respect to the conventional behaviour of ideal Schottky diodes. Experimental results show that this crossing of ln(I )-V curves is an inherent property of even Schottky diodes. The ideality factor n was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 35 publications
9
41
0
Order By: Relevance
“…Also, the ideality factor is not constant with temperature and decreased with increasing temperature. Such behavior of an ideality factor has been attributed to particular distribution of interface states and insulator layer (SiO 2 ) between metal and semiconductor [1,[24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the ideality factor is not constant with temperature and decreased with increasing temperature. Such behavior of an ideality factor has been attributed to particular distribution of interface states and insulator layer (SiO 2 ) between metal and semiconductor [1,[24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…[2,5,16,17,24,[26][27][28], since the current transport across the metal-semiconductor interface is a temperature activated process, electrons at low temperatures are able to surmount the lower barriers. In other words, more and more electrons have sufficient energy to overcome the higher barrier build up with increasing temperature and bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…It is often found that the current-voltage (I-V) characteristics of MS contacts usually deviate from the ideal thermionic emission (TE) current model [3]. Analysis of the I-V characteristics of Schottky barrier diodes (SBDs) based on TE theory usually reveals an abnormal decrease in the barrier height and an increase in the ideality factor with decreasing temperature [4,5]. The standard TE theory fails to explain this result as it expects the SBH variation to be controlled only by the variation of band gap with temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements have been carried out in the temperature range 80-300 K. It is seen that the current increases with temperature and deviates noticeably from linear trend. This behavior is due mainly to the strong dependence of both barrier height and ideality factor on temperature and partly from the nonlinearity of the Richardson plots [4,5]. As is also found, the (I-V) characteristics exhibit a crossing at high forward bias voltages and more precisely near V bias = 5.14V.…”
Section: Methodsmentioning
confidence: 52%
“…This increase in leakage current in AlGaN/GaN HEMTs is due presumably to the surface-related traps and temperature-assisted tunneling mechanism. For R s ≠ 0, Eq.1, can be rewritten as: (4) In which, R S is the series resistance and I is the thermionic current passing through the Schottky contact barrier. The series resistance can be evaluated from the forward bias current-voltage data using the method developed by Cheung [23].…”
Section: A Electrical Parametersmentioning
confidence: 99%